How financial literacy affect risk preference: an evidence from Bandung, Indonesia - Muzakky, Faqih Ahmad; Soekarno, Subiakto (Program Studi Akuntansi FPEB UPI, 2021)
Financial literacy and risk preference become issues that attracting the attention of researchers. We analyse a survey that held in Bandung, Indonesia to measure financial literacy and study its relationship on risk preference through online questionnaire. We investigate the effect of financial literacy that measured by numeracy, inflation, interest compounding, time value of money, and money illusion into set of questions that represent risk appetite indicators. As results, financial literacy shows significance relation into risk preference at 5%. Moreover, four demography factors are added for control variables in this research. Age and gender shows significance relation at 1% while marital status and formal education is not effective to affect risk preference.